Scrub typhus, a rare of cause of fulminant hepatic failure: A common disease with uncommon presentation (Indian Journal of Case Reports, 2021)
Scrub typhus (bush typhus) is a potentially lethal mite-borne, acute febrile infectious illness caused by Orientia tsutsugamushi, reported precipitating frequent outbreaks in the Asia-pacific belt. Usual presentation after a median incubation period of 10–14 days, stretches from pathognomonic eschar, high-grade fever, centrifugal skin rash, jaundice, regional lymphadenopathy to frontal headache, nevertheless complicated at times with myocarditis, acute respiratory distress syndrome, acute kidney injury, encephalitis, and shock. Although patients with scrub typhus invariably do display mild liver injury, fulminant hepatic failure (FHF) is rarely reported. We describe herein, a case of FHF in an elderly male that responded well to antibiotics. Early diagnosis and sensitive antibiotic administration aids in mortality prevention of the former.